Stability Assessment of Earth Retaining Structures under Static and Seismic Conditions - Sanjay Nimbalkar; Anindya Pain; Syed Mohd Ahmad; Qingsheng Chen (Infrastructures, 2019)
An accurate estimation of static and seismic earth pressures is extremely important in geotechnical design. The conventional Coulomb’s approach and Mononobe-Okabe’s approach have been widely used in engineering practice. However, the latter approach provides the linear distribution of seismic earth pressure behind a retaining wall in an approximate way. Therefore, the pseudo-dynamic method can be used to compute the distribution of seismic active earth pressure in a more realistic manner. The effect of wall and soil inertia must be considered for the design of a retaining wall under seismic conditions. The method proposed considers the propagation of shear and primary waves through the backfill soil and the retaining wall due to seismic excitation. The crude estimate of finding the approximate seismic acceleration makes the pseudo-static approach often unreliable to adopt in the stability assessment of retaining walls. The predictions of the active earth pressure using Coulomb theory are not consistent with the laboratory results to the development of arching in the backfill soil. A new method is proposed to compute the active earth pressure acting on the backface of a rigid retaining wall undergoing horizontal translation. The predictions of the proposed method are verified against results of laboratory tests as well as the results from other methods proposed in the past.